Millimeter wave generation for 6G applications through supercontinuum spectrum in highly nonlinear fibers with an SOA-based ring cavity laser system - Muthudurai, Sindhu; Avaninathan, Sivanantharaja; Sakkarai, Selvendran; Kadarkarai, Esakki Muthu (Oficyna Wydawnicza Politechniki Wrocławskiej, 2025)
The development of 6G wireless networks aims to provide high-speed, low-latency communication, with millimeter-wave frequencies (from 30 to 300 GHz) crucial for enabling high-capacity communication. These frequencies offer significant bandwidth but present challenges in signal generation and processing. A promising solution is the use of supercontinuum (SC) generated in highly nonlinear fibers (HNLF), the nonlinear optical process which creates broad spectral outputs spanning multiple frequency bands. HNLFs, with their high nonlinearity and dispersion properties, facilitate wideband optical spectra when subjected to high-intensity pulses. In this study, we explore supercontinuum generation using a semiconductor optical amplifier (SOA) to produce high-intensity pulses at 1550 nm, injected into a 4-meter-long HNLF. The proposed system generates a supercontinuum spectrum with average power of 31 dBm and peak pulse width of 0.008 ps, spanning from 1529 nm to over 1570 nm. The SOA in the ring cavity is optimized to generate supercontinuum without needing an external laser or pump source. The HNLF output is then detected by a photodetector to produce millimeter-wave signals. The system generates signals over a 1 GHz–5 THz range, with an output power of 39.9 dBm at 30 GHz, making it self-sustaining without an external laser.
Optica Applicata, Vol. 55, 2025, nr 2, s. 241-255
Optica Applicata is an international journal, published in a non-periodical form in the years 1971-1973 and quarterly since 1973. From the beginning of the year 2008, Optica Applicata is an Open Access journal available online via the Internet, with free access to the full text of articles serving the best interests of the scientific community. The journal is abstracted and indexed in: Chemical Abstracts, Compendex, Current Contents, Inspec, Referativnyj Zhurnal, SCI Expanded, Scopus, Ulrich’s Periodicals Directory
http://opticaapplicata.pwr.edu.pl/
Keywords: optyka; supercontinuum generation; highly nonlinear fiber; semiconductor optical amplifier; millimeter wave generation